2018
DOI: 10.1101/307108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethane-dependent synthesis of polyhydroxyalkanoates by the obligate methanotrophMethylocystis parvusOBBP

Abstract: (250 words) 18Under conditions of nutrient-limited growth, Type II obligate methanotrophs oxidize C 1 19 compounds, such as methane or methanol and accumulate intracellular granules of poly(3-20 hydroxybutyrate) (P3HB). Here, we report that, under same nutrient-limited conditions, the Type 21 II obligate methanotroph Methylocystis parvus OBBP can use ethane as its sole carbon and 22 energy source for synthesis P3HB granules, accumulating up to 35 ± 4 wt% P3HB.13 C-NMR 23 spectra of the P3HB confirmed incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Jaewook et al. found that C 2 H 6 can be utilized as sole carbon and energy source for synthesizing PHAs, proposing that acetate was produced from C 2 H 6 oxidation . Acetyl-CoA synthase converted acetate into acetyl-CoA, which was further converted into PHAs through the PHA synthesis pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaewook et al. found that C 2 H 6 can be utilized as sole carbon and energy source for synthesizing PHAs, proposing that acetate was produced from C 2 H 6 oxidation . Acetyl-CoA synthase converted acetate into acetyl-CoA, which was further converted into PHAs through the PHA synthesis pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Jaewook et al found that C 2 H 6 can be utilized as sole carbon and energy source for synthesizing PHAs, proposing that acetate was produced from C 2 H 6 oxidation. 39 Acetyl-CoA synthase converted acetate into acetyl-CoA, which was further converted into PHAs through the PHA synthesis pathway. 40 Previous studies also indicate methane can be converted into volatile fatty acids (VFAs) for driving NO 3 − and BrO 3 − bio-reduction.…”
Section: Wu Et Al Reported Clomentioning
confidence: 99%